2006
DOI: 10.1016/j.mri.2005.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of single-voxel 1H-MRS in investigating the metabolism of the activated human visual cortex at 7 T

Abstract: Proton magnetic resonance spectroscopy ( 1 H-MRS) has been used in a number of studies to noninvasively assess the temporal changes of lactate in the activated human brain. However, the results have not been consistent. The aim of the present study was to test the sensitivity of 1 H-MRS during functional experiments at the highest magnetic field currently available for human studies (7 T). Stability and reproducibility of the measurements were evaluated from LCModel analysis of time series of spectra measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
144
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(178 citation statements)
references
References 22 publications
20
144
1
Order By: Relevance
“…2,3,18 During the stimulation period (STIM), the red-black checkerboard, flickering at a frequency of 7.5 Hz and covering the central visual field of view (22 × 29 degrees), was projected on the mirror mounted to the head radio frequency (RF) coil. During the resting condition (REST), only the black background was presented.…”
Section: Visual Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,18 During the stimulation period (STIM), the red-black checkerboard, flickering at a frequency of 7.5 Hz and covering the central visual field of view (22 × 29 degrees), was projected on the mirror mounted to the head radio frequency (RF) coil. During the resting condition (REST), only the black background was presented.…”
Section: Visual Stimulationmentioning
confidence: 99%
“…16 Such an approach allowed robust quantification of metabolite concentrations along with their functional changes not only at a group level as achieved in previous investigations, 1,2,4 but also on single subjects, thus enabling the quantification of the correlation between fMRI signals and metabolite concentrations in our group of subjects. The BOLD effect induces a line narrowing of spectra during activation, 17 on the order of 0.4 to 0.5 Hz at 7 T. 2 Since, LCModel quantification can be slightly biased by such changes in linewidth, 18 an artefactual correlation between BOLD signals and metabolite concentration changes is to be expected. In the present study, we therefore assessed the spectral linewidth changes occurring during the functional paradigm for each studied subject rather than at a group level.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key inhibitory metabolites is γ‐aminobutyric acid (GABA), which is the main inhibitory neurotransmitter of the brain and is believed to have a direct impact on BOLD contrast through regulation of neuronal firing rates 6, 7, 8. In the human brain in vivo , the relationship between GABA and BOLD signals has been investigated in studies that combined fMRI and MRS 7, 9, 10, 11, 12, 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…At 7 T, the high signal-to-noise ratio (SNR) and increased spectral dispersion are expected to result in a higher precision of metabolite quantitation and this could allow for investigations of smaller voxel sizes, which better match a specific brain anatomy. However, spectral overlap with the larger resonances of the myo-inositol still hampers the detection of glycine and previous MRS studies performed at 7 T reported no detection of glycine [9,10].…”
Section: Introductionmentioning
confidence: 99%